LA SUPERACIÓN PROFESIONAL DE LOS MAESTROS PRIMARIOS DE LA ESCUELA RURAL - Naury Silva Téllez; Isabel Alfonso Cruz (University of Las Tunas, 2018)
En el artículo se realiza un análisis de las principales vías de superación, que a partir de la experiencia en su aplicación contribuyen a elevar la preparación del maestro de las escuelas multigrado, se exponen sus características psicopedagógicas generales, y se expresa cómo se revierte en una contribución al desarrollo integral de los educandos del contexto educativo rural. ABSTRACT This article is an analysis of the main ways of postgraduate training that from our experience in its implementation contribute to the professional development of teachers of multigrade schools. There are exposed general psychoeducational characteristics that contribute to the integral development of students of rural educational contexts. KEYWORDS: postgraduate training, efficiency, professional activities, rural teachers, multigrade.